Effect of 15 BMI-Associated Polymorphisms, Reported for Europeans, across Ethnicities and Degrees of Amerindian Ancestry in Mexican Children - Costa-Urrutia, Paula (Int J Mol Sci, 2020)
In Mexico, the genetic mechanisms underlying childhood obesity are poorly known. We evaluated the effect of loci, known to be associated with childhood body mass index (BMI) in Europeans, in Mexican children from different ethnic groups. We performed linear and logistic analyses of BMI and obesity, respectively, in Mestizos and Amerindians (Seris, Yaquis and Nahuatl speakers) from Northern (n = 369) and Central Mexico (n = 8545). We used linear models to understand the effect of degree of Amerindian ancestry (AMA) and genetic risk score (GRS) on BMI z-score. Northern Mexican Mestizos showed the highest overweight-obesity prevalence (47.4%), followed by Seri (36.2%) and Central Mexican (31.5%) children. Eleven loci (SEC16B/rs543874, OLFM4/rs12429545/rs9568856, FTO/rs9939609, MC4R/rs6567160, GNPDA2/rs13130484, FAIM2/rs7132908, FAM120AOS/rs944990, LMX1B/rs3829849, ADAM23/rs13387838, HOXB5/rs9299) were associated with BMI and seven (SEC16B/rs543874, OLFM4/rs12429545/rs9568856, FTO/rs9939609, MC4R/rs6567160, GNPDA2 rs13130484, LMX1B/rs3829849) were associated with obesity in Central Mexican children. One SNP was associated with obesity in Northern Mexicans and Yaquis (SEC16B/rs543874). We found higher BMI z-score at higher GRS (β = 0.11, p = 0.2 × 10(−16)) and at lower AMA (β = −0.05, p = 6.8 × 10(−7)). The GRS interacts with AMA to increase BMI (β = 0.03, p = 6.08 × 10(−3)). High genetic BMI susceptibility increase the risk of higher BMI, including in Amerindian children.